2009
DOI: 10.1158/1078-0432.ccr-08-2525
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle Modulates Ovarian Carcinoma Growth

Abstract: Purpose: The effects of reproductive hormones on ovarian cancer growth are not well understood. Here, we examined the effects of estrous cycle variation and specific reproductive hormones on ovarian cancer growth. Experimental Design: We investigated the role of reproductive hormones in ovarian cancer growth using both in vivo and in vitro models of tumor growth. Results: In vivo experiments using the HeyA8 and SKOV3ip1 ovarian cancer models showed that tumor cell inoculation during proestrus significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…These findings support the recent population-based study and other meta-analyses that imply prognostic impact of estrogen as a pro-oncogenic factor in ovarian cancer [10,13]. Molecularly, our data also support previous pre-clinical data that showed that the mechanisms of tumor progression in women with estrogen exposure occur as a result of direct tumor growth via VEGF induction and indirect growth via MAPK signaling in the tumor microenvironment [15][16][17][18]. However, a recent study including 1,742 women with HGSOC did not find that estrogen receptor expression itself was a significant predictor of survival [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings support the recent population-based study and other meta-analyses that imply prognostic impact of estrogen as a pro-oncogenic factor in ovarian cancer [10,13]. Molecularly, our data also support previous pre-clinical data that showed that the mechanisms of tumor progression in women with estrogen exposure occur as a result of direct tumor growth via VEGF induction and indirect growth via MAPK signaling in the tumor microenvironment [15][16][17][18]. However, a recent study including 1,742 women with HGSOC did not find that estrogen receptor expression itself was a significant predictor of survival [8].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, this increased risk of ovarian cancer with estrogen use was seen for serous histology [13,14]. Mechanistically, two molecular pathways have been proposed to explain ovarian cancer growth, metastasis, and progression related to estrogen: (i) tumor production of vascular endothelial growth factor (VEGF) via estrogen receptor signaling (direct pathway); and (ii) increased tumor-endothelial cell migration via mitogen-activated protein kinases (MAPK) signaling (in direct pathway) [15][16][17][18]. In contrast, a recent large-size multicenter consortium study concluded that estrogen receptor expression in HGSOC did not impact survival outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the recent population-based study and other meta-analyses that imply prognostic impact of estrogen as a pro-oncogenic factor in ovarian cancer [10,13]. Molecularly, our data also support previous pre-clinical data that showed that the mechanisms of tumor progression in women with estrogen exposure occur as a result of direct tumor growth via VEGF induction and indirect growth via MAPK signaling in the tumor microenvironment [15-18]. However, a recent study including 1,742 women with HGSOC did not find that estrogen receptor expression itself was a significant predictor of survival [8].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, this increased risk of ovarian cancer with estrogen use was seen for serous histology [13,14]. Mechanistically, two molecular pathways have been proposed to explain ovarian cancer growth, metastasis, and progression related to estrogen: (i) tumor production of vascular endothelial growth factor (VEGF) via estrogen receptor signaling (direct pathway); and (ii) increased tumor-endothelial cell migration via mitogen-activated protein kinases (MAPK) signaling (in direct pathway) [15-18]. In contrast, a recent large-size multicenter consortium study concluded that estrogen receptor expression in HGSOC did not impact survival outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with other reports, which suggest that E2 bound ERa induced cell proliferation via activation of ERK and Akt. [12][13][14]32 Cisplatin induces activation of the ERK and Akt cascades, which promote cell survival and correlate with platinum resistance. 33 However, it was not previously known that cisplatin activates ERa in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%